3:16 : the numbers of hope - Lucado, Max. (Nashville, Tenn. : Thomas Nelson, 2007)
Offers a word-by-word study of one of the best known passages in the Bible, grounding the verse in the greater context of who Jesus was.
The most famous conversation in the Bible -- No one like Him : "For God so loved the world ..." -- Hope for the hard heart : "For God so loved the world ..." -- When you get booted out : "For God so loved the world ..." -- The only one and only : " ... He gave his one and only son ..." -- The heart he offers : " ... He gave his one and only son ..." -- Heaven's "whoever" policy : " ... whoever believes in Him shall not perish ..." -- Believe and receive : " ... whoever believes in him shall not perish ..." -- God's gracious grip : " ... whoever believes in Him shall not perish ..." -- Hell's supreme surprise : " ... whoever believes in Him shall not perish ..." -- What makes heaven heavenly : " ... shall not perish but have eternal life" -- The last word on life : " ... shall not perish but have eternal life" -- Conclusion : the 3:16ed life.
Includes bibliographical references (pages 215-219).
Read by Wayne Shepherd.
Keywords: Bible -- Criticism, interpretation, etc; Salvation -- Christianity; God -- Love; Bible; God -- Love; Salvation -- Christianity; Criticism, interpretation, etc